The polysemy of container pseudo-partitives - Duek, Karen; Brasoveanu, Adrian (Proceedings of Sinn und Bedeutung, 2019)
In a series of experimental studies, we investigate the nature of the meaning multiplicity associated with container pseudo-partitives, e.g., glass of water can refer to the container (the glass) or the containee (the portion of water), asking if its distinct interpretations are available simultaneously in copredication environments or if they are in competition. The studies compare the acceptability of container pseudo-partitives to lexical polysemes (book) and homonyms (date), for which copredication has been claimed to be licit and anomalous respectively, and show that pseudo-partitives behave more like polysemes than homonyms, which is unexpected for current accounts. But we also see that copredication with pseudo-partitives is acceptable to a lesser extent than with polysemes, pointing to the possibility that copredication should be rethought in terms of the gradient costs it imposes, and that the multiple meanings of phrasal polysemous expressions like pseudo-partitives might be asymmetrically available in copredication environments.